The City & Guilds Textbook : Level 2 Diploma in Site Carpentry and Bench Joinery - Fearn, Colin; Raine, Stuart; Taylor, Tim (Construction programme manager); City and Guilds of London Institute (London : City & Guilds, 2014)
No further information has been provided for this title.
Includes index.
Formerly CIP.
Keywords: Carpentry -- Examinations -- Study guides